2019
DOI: 10.1111/pcn.12856
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and motherhood

Abstract: The primary aim of this study was to analyze the impact of schizophrenic disorders on pregnancy outcomes. The secondary aim was to briefly analyze the potential role of antipsychotic treatment on influencing pregnancy outcomes in expectant mothers with schizophrenia. We searched the MEDLINE, PsycINFO, and http://Science.gov databases for articles published in English from January 1980 to January 2019. We used the following search terms: ‘schizophrenia’, ‘motherhood’, ‘pregnancy/foetal/neonatal outcomes’, and ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 79 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…This study also confirmed the slightly increased risk for prematurity suggested by previous studies [37,[49][50][51][52]. There is probably an effect of the underlying disease and lifestyle factors behind the association seen between an increased risk for moderate to late prematurity.…”
Section: Key Resultssupporting
confidence: 91%
“…This study also confirmed the slightly increased risk for prematurity suggested by previous studies [37,[49][50][51][52]. There is probably an effect of the underlying disease and lifestyle factors behind the association seen between an increased risk for moderate to late prematurity.…”
Section: Key Resultssupporting
confidence: 91%
“…Close liaison between psychiatry and obstetrics will ensure adherence to prenatal directives, important for the prevention of obesity, diabetes and potential complications of pregnancy. Ensuring adequate housing and psychosocial support for pregnant and postpartum women with schizophrenia is a critical element of care [69,70].…”
Section: Treatment Of Schizophrenia During the Perinatal Periodmentioning
confidence: 99%
“…[7][8][9][10][11][12] Some studies have indicated that schizophrenia itself might be connected to an increased risk of malformations, and discontinuation of drug therapy is not recommended during pregnancy due to the risk of relapse of the underlying condition. [13][14][15][16][17][18] Fetal exposure to antipsychotics has in smaller cohorts been linked to increased risks of prematurity, altered fetal growth, increased admission to neonatal intensive care unit (NICU), low APGAR scores, and neonatal extrapyramidal and respiratory symptoms. These risks seem to increase with increased dosage and with polypharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment during pregnancy does not generally seem to increase the risk of malformations 7–12. Some studies have indicated that schizophrenia itself might be connected to an increased risk of malformations, and discontinuation of drug therapy is not recommended during pregnancy due to the risk of relapse of the underlying condition 13–18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation